Pengaruh Penambahan CuO Sebagai Sintering Aid pada Elektrolit Padat Neodymium Doped Ceria (NDC) - Anindityo Anindityo Arifiadi; Syoni Soepriyanto (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2019)
In this research, NDC powder with a chemical formula of Ce0,75Nd0,25O1,875 added with 0, 0,5, 1, ad 1,5 wt% CuO is synthesized. Powder is mixed by stirring at an ethanol medium. Mixed powder is compacted to form a pellet and then sintered at 1000oC, 1200oC, and 1400oC for 4 hours. Sintering time variation of 2, 3, and 4 hours is also performed at 1200oC. Result shows that the highest relative density of 65,21% is achieved by 0,5wt% CuO addition sintered at 1200oC for 4 hours. Without CuO addition, pellet shrink through grain boundary diffusion and with CuO addition, liquid phase sintering occurs. Electrochemical impedance analysis shows that CuO lowers grain boundary resistance. The highest conductivity (1,52 x 10-2 S/cm) at 700oC with an activation energy of 0,85 eV is achieved by pellet added with 0,5 wt% CuO.